INDIKATOR CUSTOMER LOYALTY BERDASARKAN CONFIRMATORY FACTOR ANALYSIS PERUSAHAAN DISTRIBUSI GAS ALAM SURABAYA - Aji Rahayu; Ristanti Akseptori; Danis Maulana (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
The business world is now increasingly competitive which requires business people to always be active in developing their business. A natural gas distribution company in Surabaya is one of the companies that must continue to exist in today’s business world. To attract customers, companies do many ways. One of them is adding a program called Gas Kita Pintar Residential (GPiR) which is aimed at household customers. In the courseof this program it can be seen that it tends to be stable and there has been a significant increase in subscribers. Thats indicates customer loyalty. Customer loyalty has three indicators there is customer value, customer satisfaction and customer trust. The aim of the research was find out how big contribution of the indicators is to the variables. The results of this study indicate that the three indicators show a fit match based on the goodness of fit criteria and all indicators that have the highest level of factor loading are Customer Trust. Then this study uses the Confirmatory Factor Analysis.